Influence of malting and fermentation on the nutritional composition, thermal stability, structural and physicochemical properties of a gluten-free flour blend of Digitaria exilis (Fonio) and date fruits - Oluwatobi Victoria Obayomi; Abiola Folakemi Olaniran; Stephen Olugbemiga Owa (Applied Food Research)
Childhood malnutrition is one of the major public health challenges in low- and middle-income countries. In this study, fonio and date flour blends were prepared and the effect of organic processing methods (fermentation and malting) and fortification on nutrient composition, structural and thermal stability was investigated. The fonio flour samples were subjected to different treatments: fonio flour sample (FFS control), fermented fonio flour (FFF), fermented fonio flour with thirty percent date fruit powder (FFDF), malted fonio flour (MFF) and malted fonio flour with thirty percent date fruit powder (MFDF). The results showed significant changes in the proximate composition. The protein content ranged from 1.77 in FFS to 3.13 % in MFF, while the fat content fat content increased significantly with the addition of date fruit, reaching 1.10 % in MFDF. The dietary fiber content also increased, with MFDF having the highest value (1.50 %). The ash content ranged from 0.77 % in FFF to 2.03 % in MFDF, and carbohydrates decreased from 86.4 in FFS to 81.46 % in MFDF. The mineral analysis showed that the addition of malt and dates significantly increased the mineral content. The calcium content increased from 130.00 in FFS to 206.67 mg/100 g in MFDF, while the iron content increased from 5.27 in FFS to 9.60 mg/100 g in MFDF. Magnesium content ranged from 33.33 in FFS to 85.00 mg/100 g in MFDF, and zinc content increased from 0.04 in FFS to 0.17 mg/100 g in MFDF. Fourier transform infrared (FTIR) spectra showed changes and enhancements in band intensities, while scanning electron microscopy (SEM) revealed changes in microstructure due to fermentation and malting. X-ray diffraction showed that the combination of malting and enrichment with date powder increased the loss of crystallinity due to enzymatic hydrolysis and the amorphous nature of the date components. TG-DTA analyzes showed remarkable variations in degradation temperature. These results suggest that fermentation, malting and fortification with date fruit powder significantly improve the nutrient and mineral profiles as well as the structure and thermal stability of fonio flour, and thus represent a valuable strategy to improve the quality of fonio-based foods.